(untitled) (Research, Society and Development, 2025)
The TP53 p.Arg337His is a founder mutation that exists at a very high frequency in Southern and Southeastern Brazil. Adrenocortical and plexus choroides carcinomas are highly associated with this variant. The present scoping review protocol aimed to map health-related literature searching for pediatric cancer related to the TP53 p.Arg337His. Methods: A scoping review protocol is presented in this article, conducted adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR) guideline. Six databases, an electronic repository, and additional sources were searched using keywords and text words. The review team consists of three independent screeners. Two screeners will do the initial title and abstract screening for all studies retrieved by the search strategy and then the full text screening phase. Reference lists of included studies will be screened, and data will be independently extracted by the review team. Results will be analyzed qualitatively and quantitatively. Ethics and dissemination: Ethical approval is not necessary, since the study does not involve human participants. Findings will be disseminated through publication at scientific journals and conferences.